Sporting Activity Is Reduced 11 Years After First-Generation Autologous Chondrocyte Implantation in the Knee Joint. (October 2017) - Erdle, Benjamin; Herrmann, Simon; Porichis, Stella; Uhl, Markus; Ghanem, Nadir; Schmal, Hagen; Suedkamp, Norbert; Niemeyer, Philipp; Salzmann, Gian M.
Background: Little is known about long-term sporting activity after periosteal autologous chondrocyte implantation (ACI-P) and its correlation to clinical, morphological, and ultrastructural cartilage characteristics on magnetic resonance imaging (MRI). Purpose: To evaluate long-term sporting activity after ACI-P and to correlate with clinical and MRI findings. Study Design: Case series; Level of evidence, 4. Methods: Patients who underwent ACI-P for isolated cartilage defects of the knee joint between 1997 and 2001 were analyzed for sporting ability for 3 different time points: lifetime until the onset of pain, the year before ACI-P, and 11 years (range, 9.0-13.4 years) postoperatively. Sporting activity was assessed and patients' level of activity scaled using standardized questionnaires. MRI scans of the affected knee joint at follow-up were analyzed using the MOCART (magnetic resonance observation of cartilage repair tissue) score and T2 mapping. Results: Seventy of 86 patients (81% follow-up rate) consisting of 25 female and 45 male patients, with a mean age of 33.3 ± 10.2 years at the time of surgery, mean defect size of 6.5 ± 4.0 cm 2, and 1.17 treated defects per patient, agreed to participate in the study at a mean 10.9 ± 1.1 years after ACI-P. Fifty-nine patients (69% of total; 84% of follow-up) agreed to MRI, allowing the complete evaluation of 71 transplant sites. Before the onset of symptoms (lifetime), 95.7% of patients played a mean 6.0 sporting activities at a competitive level. In the year before ACI-P, 81.4% of patients played a mean 3.4 sporting activities in 2.4 sessions during 5.4 hours per week at a recreational level. At follow-up, 82.9% of the patients played a mean 3.0 sporting activities in 1.8 sessions during 3.0 hours per week at a recreational level. In contrast to objective factors, 65.6% of the patients felt that their subjective sporting ability had improved or strongly improved after ACI-P, whereas 12.9% felt that their situation had declined or strongly declined, and 21.4% stated that their sporting ability had undergone no change because of surgery. Factors of sporting activity correlated significantly with clinical long-term outcomes. MRI analysis with a mean repair tissue T2 relaxation time of 35.2 milliseconds and mean MOCART score of 44.9 showed no conclusive significant correlation to sporting activity. Level of performance was the only sporting activity factor to show a weak correlation with subgroups of the MOCART score. Conclusion: The premorbid level of sporting and recreational activities cannot be achieved 11 years after ACI-P. The MRI results determined at this time point did not conclusively correlate with long-term sporting activity.